Antioxidants and mucosa protectives: realistic therapeutic options in inflammatory bowel disease?. Issue 3 (1998) - Kruidenier, L.; Verspaget, H. W.
Abstract : Oxidative damage is involved in the pathogenic process of idiopathic chronic inflammatory bowel disease. Although specific intervention in the oxidative cascade showed promising results in animal models and preliminary patient trials, the clinical efficacy of antioxidants still has to be established. Mucosa protection, for example by dietary fatty acids, seems to attenuate the intestinal inflammatory process as well but awaits definite clinical proof for the treatment of inflammatory bowel disease